The end of the line for today's wind turbines - Kolios, Athanasios; Martinez Luengo, Maria (Elsevier, 2016)
We need to start thinking today about the future of our wind turbines, according to Dr Athanasios Kolios and María Martínez-Luengo from Cranfield University. EDF's recent announcement that they will extend the life of 4 of their 8 UK-based nuclear power plants has focussed analyst's minds on the pros and cons of extending service life. There are numerous cost and engineering issues at play here. These obviously include balancing the initial investment cost against profits already made and the potential decreasing efficiency alongside the increasing maintenance costs in an ageing facility. The issues cut across the whole energy sector, but they aren’t something many of our renewable technologies have yet had to face.